The Origins of Creationism in the Netherlands: The Evolution Debate among Twentieth-Century Dutch Neo-Calvinists - Flipse, Abraham C. (Church history, 2012)
The Netherlands is, besides the United States, one of the few countries where debates about creationism have been raging for decades. Strict creationism has become deeply rooted in traditional Reformed (Calvinist) circles, which is all the more remarkable as it stemmed from a very different culture and theological tradition. This essay analyses the historical implantation of this foreign element in Dutch soil by investigating the long-term interaction between American creationism and Dutch “neo-Calvinism,” a movement emerging in the late nineteenth century, which attempted to bring classical Calvinism into rapport with modern times. The heated debates about evolution in the interbellum period as well as in the sixties—periods characterized by a cultural reorientation of the Dutch Calvinists—turn out to have played a crucial role. In the interbellum period, leading Dutch theologians—fiercely challenged by Calvinist scientists—imported US “flood geology” in an attempt to stem the process of modernisation in the Calvinist subculture. In the sixties many Calvinists abandoned their resistance to evolutionary theory, but creationism continued to play a prominent role as the neo-Calvinist tradition was upheld by an orthodox minority, who (re-)embraced the reviving “Genesis Flood” creationism. The appropriation of American creationism was eased by the earlier Calvinist-creationist connection, but also by “inventing” a Calvinist-creationist tradition, suggesting continuity with the ideas of the founding fathers of neo-Calvinism. This article aims to contribute to a better understanding of what Ronald L. Numbers has recently called the “globalization” of the “science-and-religion dialogue.”